Quebec’s English-Speaking Community and the Partnership Approach of Its Networks in Health - Pocock, Joanne (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted.